Women in the Boardroom and Their Impact on Climate Change Related Disclosure - Momin, M; Hossain, M; Farooque, O; Almotairy, O (Emerald, 2017)
Purpose - This paper aims to investigate the relationship between gender diversity and the Carbon Disclosure Project (CDP) score/index. Specifically, the study describes extant research on theoretical perspectives, and the impact of women on corporate boards (WOB) on carbon emission issues in the global perspective. Design/methodology/approach - This study uses the carbon disclosure scores of the Carbon Disclosure Project (CDP) from 2011 to 2013 (inclusive). A total observation for the three year periods is 1175 companies. However, based on data availability for the model, our sample size totals 331 companies in 33 countries with firms in 12 geographical locations. We used a model which is estimated using the fixed-effects estimator. Findings -The outcomes of the study reveal that there is a positive relationship between gender diversity (WOB) and carbon disclosure information. In addition to establishing a relationship between CDP score and other control variables, this study also found a relationship with Board size, asset size, energy consumption, and Tobin’s Q, which is common in the existing literature. Research limitations/implications -The limitations of the study mostly revolve around samples and the time period. To further test the generalizability and cross-sectional validity of the outcomes, it is suggested that the proposed framework be tested in more socially responsible firms. Practical implications -There are increasing pressures for WOBs from diverse stakeholders, such as the European Commission, national governments, politicians, employer lobby groups, shareholders, Fortune and FTSE rankings and best places for women to work lists. The study offers insights to policy makers implementing gender quota legislation. Originality/value -The study has important implications for putting into practice good corporate governance and in particular, gender diversity. The outcomes of our analyses advocate that companies that included women directors and with a smaller board size may expect to achieve a higher level of carbon emission performance and to voluntarily disclose the level of carbon information assessment requested by the CDP.
Keywords: Climate change; Carbon disclosure project; GHG; Corporate social responsibility; Women on corporate board